Niezdolność absolutna czy również niezdolność relatywna? - Stawniak, Henryk (Prawo Kanoniczne, 2011)
The article will be concerned the consensus inability from Can. 1095 No. 3 of the Code of Canon Law from 1983. The main theme issue asks the question if the nullity of the marriage causes only the absolute inability of the counterparty, i.e., preventing intended from taking the essential obligations of marriage regardless of who provides marriage, or whether it also causes the inability invalid relative, i.e., preventing intended from undertaking these obligations only in relation to a particular partner. Because there is the agreement among the canonists and ecclesiastical judges as to whether the inability to take significant absolute responsibilities, so understood, invalidate the marriage, it actually boils down to the question whether the relative inability is to be taken into the account when determining the invalidity of the can. 1095 No. 3 of the Code of Canon Law? It is possible to identify the supporters and opponents of the opinion on the relevance of incapacitas relativa, both in doctrine and in jurisprudence. But they are in the vast minority. The article presents their arguments and signalizes the errors or dangers which include the thesis about the relative adequacy of incapacity. Because the key to resolving the issue are the concepts of the marriage, its nature, subject to consent so the compilation begins with these issues in the context of the obstacles impotence (impotentia coeundi).